Environmental and Social Management System Implementation Handbook : Health Care Facilities - International Finance Corporation (World Bank, Washington, DC, 2015)
Today, health care facilities are confronted with a number of significant envi-ronmental and social challenges. None of the challenges is insurmountable, but if not effectively assessed and managed, they will hurt the quality of your patient care, profitability, reputation, and prospects for future sustainability. Among these challenges are the increasing cost of energy and water, the grow¬ing power and influence of regulatory agencies, and rapidly evolving commu¬nity awareness and concerns about environmental and social issues. These risks are in addition to the primary risk of failing to provide high-quality health care or build patient confidence. All of these risks ultimately have financial consequences and are driving forces that should motivate you to implement a management system for your health care facility. A management system will enable you to consistently foresee and address issues confronting your facility so you can prevent potential risks from becoming actual problems. Implementing an environmental and social management system (ESMS) can have direct financial benefits. Conserving and using energy and water more efficiently helps to reduce operational costs.